2020
DOI: 10.1186/s13071-020-3998-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infectivity of Plasmodium vivax to wild-caught and laboratory-adapted (colonized) Anopheles arabiensis mosquitoes in Ethiopia

Abstract: Background: Mosquito-feeding assays that assess transmission of Plasmodium from man-to-mosquito typically use laboratory mosquito colonies. The microbiome and genetic background of local mosquitoes may be different and influence Plasmodium transmission efficiency. In order to interpret transmission studies to the local epidemiology, it is therefore crucial to understand the relationship between infectivity in laboratory-adapted and local mosquitoes. Methods: We assessed infectivity of Plasmodium vivax-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
(79 reference statements)
2
9
1
Order By: Relevance
“…Several factors are known to influence the variation in mosquito infection, including gametocytes density [ 44 ] and the presence of host immunity [ 45 ]. A positive association between gametocyte density and infectivity has been discovered in several other studies [ 9 , 43 , 46 ] but was not observed in the present study. This finding may reflect the presence of transmission-blocking components in the blood of Indian patients.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Several factors are known to influence the variation in mosquito infection, including gametocytes density [ 44 ] and the presence of host immunity [ 45 ]. A positive association between gametocyte density and infectivity has been discovered in several other studies [ 9 , 43 , 46 ] but was not observed in the present study. This finding may reflect the presence of transmission-blocking components in the blood of Indian patients.…”
Section: Discussioncontrasting
confidence: 56%
“…stephensi with Plasmodium parasite blood [ 42 ]. The higher feeding efficiency of the colony compared with wild mosquitoes has also been reported for Anopheles arabiensis , and a longer starvation period is also preferred for wild-caught mosquitoes [ 43 ]. This finding guides the use of laboratory-colonized mosquitoes in feeding experiments, which offers a significant advantage over the use of wild mosquitoes in terms of logistics, ease of maintenance and handling, and scaling-up flexibility and reproducibility of the assays [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of human blood samples naturally infected with P. vivax in mosquito-feeding assays allowed us to mimic natural infection events as they would occur in nature, making results of this study pertinent to the interpretation of data from field-collected Anopheles [ 29 ] using these methods for Plasmodium detection . The collection method of wild Anopheles and site-specific endemicity are important considerations in the interpretation of PCR-derived infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…The use of human blood samples naturally infected with P. vivax in mosquito-feeding assays allowed us to mimic natural infection events as they would occur in nature, making results of this study pertinent to the interpretation of data from eld-collected Anopheles [29] using these methods for Plasmodium detection. The collection method of wild Anopheles and site-speci c endemicity are important considerations in the interpretation of PCR-derived infection rate.…”
Section: Discussionmentioning
confidence: 99%